Avoidance of contaminated sediments by an amphipod (Melita plumulosa), A harpacticoid copepod (Nitocra spinipes), and a snail (Phallomedusa solida). (17th January 2013) - Ward, Daniel J.; Simpson, Stuart L.; Jolley, Dianne F.
Abstract The distribution of contaminants is seldom homogeneous in aquatic systems. In the present study, the avoidance response of Melita plumulosa, Nitocra spinipes, and Phallomedusa solida when exposed to contaminated sediments was investigated. Test vessels were designed to allow the congruent placement of two sediments and assessment of the movement of organisms between the sediments. When exposed to reference sediment, each species dispersed evenly between test chambers regardless of differences in sediment particle size. In the presence of contaminated sediment, the magnitude and rate of avoidance varied. Avoidance assays showed that test species avoided contaminated sediment as early as 6, 6, and 24 h following exposure for N. spinipes, P. solida, and M. plumulosa, respectively. The 48‐h avoidance response of M. plumulosa for nine contaminated sediments of varying toxicity showed that avoidance was generally greater for sediments which elicited greater 10‐d lethality to this species. The study demonstrated that each of these species has the ability to respond to chemical cues in the environment to inhabit sediment that provides the best opportunity for survival. The avoidance response for each species indicates the potential for developing rapid screening methods to assess sediment quality. Evidence suggests that avoidance was related to sediment toxicity and that static 10‐d toxicity methods are likely to overestimate toxicity for species, which would avoid contamination in heterogeneous field settings. Environ. Toxicol. Chem. 2013;32:644–652. © 2012 SETAC